Novel Temperature-Based Topological Indices for Certain Convex Polytopes (Contemporary Mathematics, 2024)
A topological index is a number that assists in understanding various physical characteristics, chemical reactivities, and boiling activities of a chemical compound by characterizing the whole molecular graph structure. These indices are essential for quantifying different chemical properties of chemical compounds in chemical graph theory. The choice of convex polytopes in this work is an important feature due to its structural adaptability, easy accessibility and astonishing capacity to identify its numerical values. In this paper, we present exact analytical expressions for the general first temperature index, the general second temperature index, the first hyper-temperature index, the second hyper-temperature index, the sum-connectivity temperature index, the product-connectivity temperature index, the reciprocal product-connectivity temperature index, the arithmetic-geometric temperature index and the F-temperature index of convex polytopes.
Keywords: geometrical graph, edge partitioning, convex polytope, temperature index